Artificial intelligence capabilities in the context of the author's conception of creativity - Raikhert , Kostiantyn (Skhid, 2024)
The study provides some philosophical reflections on the creativity of artificial in-telligence. The study supposes that artificial intelligence can be considered creative only if it creates something new with help of imagination (or its equivalent) and ap-pealing to the so-called “background” (background and general knowledge, biases, competencies, experience, habits, intuition, prejudices, political preferences, skills, stereotypes, values, and others), and its creative activity must be either necessary or arbitrary. Necessary creative activity is related to the solution of specific tasks, for example, within the framework of technical invention or scientific discovery. Arbitrary creative activity is associated with spontaneous, aimless and inexpedient human activity. This type of creative activity takes place when a creative doer has free time, leisure, enthusiasm (hobby), plays a game or is bored. Based on the two types of creative activity, two types of creative artificial intelligence can be distinguished: a weak creative artificial intelligence that makes necessary creative activities related to the tool nature of artificial intelligence, specifically to effectively solving specific problems and tasks, and a strong creative artificial intelligence that makes arbitrary creative activities, that is, creates for the sake of creating alone. The strong creative artificial intelligence can be possible only if the artificial intelligence is given autono-my, the freedom to manage that autonomy, and learns to manage its freedom.